Pelatihan dan Pendampingan Guru Matematika pada Pemanfaatan Artificial Intelligence untuk Penyusunan Desain Pembelajaran - Hendarto Cahyono; Moh. Mahfud Effendi; Siti Khoiruli Ummah; Dian Devita Yohanie (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Artificial Intelligence (AI) plays a role in learning to create fast, practical and interesting learning designs. However, not all educators are able to use and organize the layout of the learning design created by AI. The problems of partners, namely vocational high school teachers, conveyed through FGDs include 1) the need for cooperation with universities to improve the quality of learning in vocational high schools, 2) AI has not been used wisely by students, and 3) teachers have difficulty in designing interesting learning designs and utilizing technology. Based on the problems that occur in schools, the focus of the community service program is the use of AI to design learning. The implementation method as well as the solution offered is by providing teacher training to design learning designs and assisting teachers in using AI. The stages of implementation include FGDs with the school regarding the scheduling and target achievements of each program, training, mentoring and evaluation. Community service activities involved 17 teachers from various subjects. The results of the community service are that teachers are able to utilize AI in compiling learning designs that include teaching modules, LKPD, quizzes and assessment rubrics. The AI ​​applications used include ChatGPT, MagicSchoolAI, and Gemini. Teachers said that the use of AI makes teachers' administrative work easier and faster. In addition, students appear more interested in using learning media created using AI.